To get all the terms with "x" on the same side, we need to combine like terms. We start by moving the terms with "x" to the left side of the equation:
5x - 12 - 6x = -10x + 7 - 1
Combine the "x" terms on the left side of the equation:
(5x - 6x) - 12 = -10x + 7 - 1
-x - 12 = -10x + 6
Next, move the constant terms to the right side of the equation:
-x - 12 + 10x = 6
-12 + 9x = 6
To isolate "x," move the constant term to the left side by subtracting 6 from both sides:
-12 + 9x - 6 = 6 - 6
9x - 18 = 0
Finally, move the constant term to the right side by adding 18 to both sides:
9x - 18 + 18 = 0 + 18
9x = 18
Divide both sides of the equation by 9 to solve for "x":
(9x)/9 = 18/9
x = 2
Therefore, the solution is x = 2.
Get X Terms on the same side of 5x−12−6x=−10x+7−1
1 answer